STUDI KOMPARASI PEMANFAATAN MUSEUM KARTINI SEBAGAI SUMBER BELAJAR - Agam, Diky Tia (Indonesian Journal of History Education, 2014)
Jepara has a museum that can be used as a medium of learning, especially history. The museum is named Museum Kartini and can be utilized as a source of learning the history of the student. Kartini Museum as one of the museums in Jepara have collections that have the potential to serve as a source of student learning in the city of Jepara. The problems studied in this research are: (a) How do the results of social studies material history of the seventh grade students of SMP Negeri 5 Jepara Kartini Museum utilize as a source of learning? (b) How do the results of social studies material history of the seventh grade students of SMP Negeri 5 Jepara Kartini Museum does not utilize as a source of learning? (c) Are there differences in the utilization of Museum Kartini as a Learning Resource to Learning Outcomes Social education History Matter in class VII student middle school  5 Jepara, Central Java? Kabupaten Jepara memiliki sebuah museum yang dapat dijadikan sebagai media pembelajaran khususnya sejarah. Museum ini bernama Museum Kartini dan dapat dimanfaatkan sebagai sebuah sumber belajar sejarah siswa. Museum Kartini sebagai salah satu museum di Kabupaten Jepara memiliki koleksi-koleksi yang berpotensi untuk dijadikan sebagai sumber belajar siswa di kota Jepara. Permasalahan yang dikaji dalam penelitian ini adalah : (a) Bagaimana hasil belajar IPS materi Sejarah siswa kelas VII SMP Negeri 5 Jepara yang memanfaatkan Museum Kartini sebagai sumber belajar? (b) Bagaimana hasil belajar IPS materi Sejarah siswa kelas VII SMP Negeri 5 Jepara yang tidak memanfaatkan Museum Kartini sebagai sumber belajar? (c) Adakah perbedaan pemanfaatan Museum Kartini sebagai Sumber Belajar terhadap Hasil Belajar IPS Materi Sejarah pada Siswa kelas VII SMP Negeri 5 Jepara Jawa Tengah?